Sister Joseph Marie Nodule: A Clue to Intra-Abdominal Malignancy - Wazir, Zair Muhammad; Hayat, Zafar (Journal of Postgraduate Medical Institute, 2011)
The metastatic nodule at umbilicus – "SISTER JOSEPH MARIE NODULE" - is not an uncommon features of intra-abdominal malignancy. This should arouse a search for primary abdominal malignancy.